Prevalence of asymptomatic macrothrombocytopenia in voluntary blood donors: A multicentric study - Archana Buch; Yaminy Ingale; Tulika Chandra; Sudha Ranganathan; Sudipta Sekhar Das; Mallika Agarwal; Charusheela Gore; Madhura Gandhi (Asian Journal of Transfusion Science)
INTRODUCTION: Macrothrombocytopenia is a combination of thrombocytopenia and giant platelets (PLTs). It can be found asymptomatically with several genetic polymorphisms/mutations. This study aimed to assess the prevalence of macrothrombocytopenia in blood donors and to identify its geographic variation. MATERIALS AND METHODS: A cross-sectional observational study was conducted in blood donors in the East, West, North, and South zones of India. Donors not eligible for blood donation were excluded. Blood was collected and analyzed by hematology analyzer. Samples with low PLT count (<1.5 lakhs/mm3) and mean PLT volume >11.5 fl were identified, and a peripheral blood smear was prepared, stained, and screened for giant PLTs. The data were analyzed using MS Excel (Microsoft 365), RStudio (Version: 2023.03.1 + 446), and IBM SPSS Statistics 27. RESULTS: A total of 2574 donors were screened at four centers of different geographic zones of India. The mean age was 34.81 ± 9.32 with male: female of 34.75:1. Overall macrothrombocytopenia was found in 102 (4%) with significant zonal variation: 88 (86.3%), 4 (3.9%) in East and South, respectively, and 5 (4.9%) each in West and North regions. The peripheral smears revealed giant PLTs in all cases of macrothrombocytopenia in the South and North, 76% and 80% in the East and West, respectively. The most common blood group showing macrothrombocytopenia was B positive 41 (40.2%). CONCLUSION: Macrothrombocytopenia shows significant zonal variation, with a maximum number of cases identified in the East zone of India. Screening and awareness of this condition are essential to counsel donors for bleeding tendencies.